The Influence of Storytelling Techniques in Digital Marketing on Brand Loyalty: A Consumer Psychology Perspective - Mandung, Fitriani (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This study investigates the impact of storytelling techniques in digital marketing on brand loyalty, focusing on consumer psychology perspectives. The research aims to identify how storytelling, through emotional resonance, authenticity, and cultural relevance, fosters brand loyalty by creating deep, psychological connections with consumers. A qualitative research approach was applied, involving a systematic literature review of academic journals, books, and industry reports on storytelling, digital marketing, and consumer-brand relationships. The analysis was conducted using thematic coding, which categorized data into primary themes, including emotional engagement, brand authenticity, and cultural adaptation. Results indicate that storytelling effectively influences consumer loyalty by evoking emotional responses, establishing brand trust through authentic narratives, and enhancing engagement through culturally relevant content. Findings reveal that storytelling in digital marketing transforms brands into relatable entities, reinforcing loyalty through shared values and identity alignment. The study concludes with theoretical and managerial implications, suggesting that brands should prioritize authentic and culturally adaptive storytelling to cultivate lasting consumer loyalty in a competitive digital landscape. Future research should further examine the long-term effects of storytelling on loyalty across different digital platforms and cultural contexts.